Humanitarian Theology in Comparative Perspective: Gus Dur and Martin Luther King Jr. on Peace and Global Justice - Wandana, Arya Cipta; Masykur, Masykur; Dzawafi, Agus Ali (Program Studi Aqidah dan Filsafat Islam, 2025)
This article examines the humanitarian thought of Abdurrahman Wahid (Gus Dur) and Martin Luther King Jr. through a comparative analysis grounded in religious ethics, peacebuilding, and social justice. Both figures are widely recognized as religious leaders who translated faith-based commitments into concrete responses to injustice, yet they operated within distinct sociopolitical contexts and adopted different strategic approaches. This study employs qualitative library research and comparative content analysis to examine three analytical dimensions: theological foundations, core humanitarian principles, and the contexts in which those principles were implemented. The findings show that Gus Dur and King share a fundamental ethical convergence in treating religion as a public moral resource for defending human dignity, equality, and justice, as well as in rejecting violence as a legitimate means of social change. Gus Dur articulated humanitarian commitments through Islamic concepts such as rahmatan lil ‘alamin and al-maqasid al-shari‘ah, emphasizing pluralism, dialogue, and institutional reform within a multi-religious society. King grounded his humanitarian vision in Christian theology, particularly Imago Dei and agape, and advanced disciplined nonviolent action as a moral and strategic response to racial segregation and structural injustice. The analysis also reveals a significant divergence in operational strategy. Gus Dur primarily pursued reform through engagement with political and religious institutions, while King mobilized mass participation and moral pressure from outside the state. Read together, their approaches offer a complementary framework for contemporary humanitarian practice that links civic resistance with institutional responsibility. The study contributes to scholarship on religion-based peacebuilding by demonstrating how shared ethical commitments can generate different strategies shaped by political opportunity, social structure, and conflict configuration.